Pemulihan Luka Batin Generasi Z melalui Pendekatan REBT: Studi Integratif dan Rekonstruksi Model Konseling Pastoral Kristen - Kezia Indianti Ruhama (Jurnal Pistis: Teologi dan Praktika, 2026)
Generation Z has a high vulnerability to the phenomenon of toxic relationships due to the strong need for social validation in the digital era. The impact of this destructive relationship often leaves deep inner wounds, anxiety, and cognitive distortion in the form of irrational beliefs that erode their self-worth before God. Conventional psychological approaches such as Rational Emotive Behavior Therapy (REBT) are effective in changing irrational mindsets, but often lack the spiritual identity crisis of the victim. This research aims to construct an integration model between the REBT approach and the values of the Christian faith in the practice of pastoral counseling for the holistic healing of Generation Z's inner wounds. This research uses a qualitative approach with the library research method. The data analysis technique is carried out through three main stages: conceptual analysis of REBT, theological analysis of biblical texts, and integrative analysis to formulate contextual pastoral counseling models. The results of the study showed that the integration of the G-A-B-C-D-E model in REBT with pastoral counseling was able to transform the victim's mindset. The process of disputation is sharpened into a cognitive-spiritual (empirical-theological, logical-spiritual, and pragmatic-functional) disputation using the truth of God's word (Ps. 139:14, Rom. 12:2) to renew the mind and deconstruct the trauma of bonding. This integration resulted in an Effective New Philosophy in the form of a healthy and solid restoration of self-identity in Christ, so that Generation Z no longer relies on human validation but on God's love.